Transcribing Memories in Genome Architecture. Issue 9 (September 2019) - Tonn Eisinger, Katherine R.; West, Anne E.
Abstract : Whether dynamic changes in genome architecture underlie transcriptional and functional plasticity in mature neurons has been technically challenging to address. A recent study (Yamada et al ., Nature, 2019) exploited experimental advantages of the cerebellum to reveal cell type-specific changes in chromatin architecture that coordinate neural activity-induced changes in gene transcription and contribute to sensorimotor learning.